Evaluation of changes in myocardial perfusion and function on exercise in patients with coronary artery disease by gated MIBI scintigraphy. Issue 1 (July 1993) - Avery, P; Hudson, N; Hubner, P
Abstract : OBJECTIVE--To investigate the ability of gated methoxy-isobutylisonitrile (MIBI) scintigraphy to measure changes in myocardial function as well as perfusion with exercise. SETTING--Regional cardiothoracic centre. PATIENTS--43 presenting with chest pain, 28 with coronary artery disease on angiography, and 15 with normal coronary arteriograms. RESULTS--Gated perfusion images showed an improvement in detecting regions with stenosed arteries compared with non-gated images (38/55 v 31/55, p < or = 0.01)). Functional analysis showed an increase in fractional shortening of 4.11% in subjects with normal coronary arteries, whereas in those with coronary disease a fall of 0.57% was found (p < or = 0.01). Both perfusion and function imaging showed an improved sensitivity compared with standard exercise testing (p < or = 0.01). When both function and perfusion imaging were analysed all patients with coronary disease were detected. There was agreement in abnormal regions in 33/55 territories supplied by a stenosed artery. Combined perfusion and function detected 49/55 (89%) of abnormal regions, thus improving the overall sensitivity from 38/55 (69%) by perfusion imaging alone (p < or = 0.01). CONCLUSIONS--Gated methoxy-isobutylisonitrile scintigraphy can successfully evaluate perfusion and function on exercise, so improving the diagnostic usefulness of this agent.